Analysis of Genetic Diversity and Population Structure of Some Bangladeshi Rice Landraces and HYV - Hassan, M. M.; Shamsuddin, A. K. M.; Islam, M. M.; Khatun, K.; Halder, J. (Journal of Scientific Research, 2012)
Information on the patterns of genetic variation and population structure is essential for rational use and efficient management of germplasms. It helps in monitoring germplasm and can also be used to predict potential genetic gains. Therefore, in the present study genetic diversity of 59 rice genotypes were assessed using 8 simple sequence repeat (SSR) primers. By the DNA profiling, a total of 114 alleles were detected. Allele number per/locus ranged from 9 to 27, with an average of 14.25. Average polymorphism information content (PIC) value was 0.857 with lowest 0.767 to highest 0.857. Mean gene diversity over all SSR loci was 0.870 with a range from 0.792 to 0.948. Fst values for each locus varied from 0.071 to 0.262. Genetic distance between the variety pair ranged from 0.33 to 1.0. The lowest genetic distance was found between Rajashili and Kumragori (2). Cluster and principal coordinate analysis (PCoA) analysis revealed similar pattern of variation. Marker RM11300 was found most polymorphic and robust among the accessions and can be widely used for rice germplasm characterization. The exclusive variability and unique feature of germplasm found in this study can be a gateway for both domestic and global rice improvement. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10416 J. Sci. Res. 4 (3), 757-767 (2012)